Memórias da Colônia do Bonfim: um olhar sobre o espaço e seus significados - ARAÚJO, Nathalia do Vale Carvalho de (2023)
Leprosy, currently known as leprosy, is a public health problem with a high proportion and social impact in history, this is due to the fact of the social construction of an ancient tradition marked by an excluding and stigmatizing model with the “leprosariums” as a scenario. The Bonfim colony, a leper colony structured in the 1930s in Maranhão, configures our research object. The main objective of this work is to understand the relationship between space and memory that permeates the context of compulsory isolation in the former hospital-colony of Bonfim. The aim is to analyze the space/memory of this place, identifying the impacts of compulsory isolation on identity from the oral reports of former residents, as well as analyzing how the sociocultural dimensions of the disease and its stigma interfere in the construction of the symbolic meanings of the place, also identifying the heritage, documental and cultural collection. To do so, we dialogue with the categories of space and memory, using authors such as Pollak, Ricouer and Halbwachs, investigating memory with the contributions of the space category listed by Milton Santos. This is a qualitative research, based on the life history of egresses from the colony, the analysis of places of memory, such as the Domingas Borges Memorial, bringing the discussion about the history of Bonfim under the eyes and narrative of the former inmates.